THE EFFECT OF DIFFERENT CONCENTRATION OF CRUDE BROMELAIN ENZYM TO CATFISH (Clarias gariepinus) SAUCE - Kartika Dewi; Rahman Karnila; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was intended to determine the effect of crude bromelain enzym withdifferent concentration to catfish (Clarias gariepinus) sauce. The fuction of crude bromelainenzym as catalysator which helping of hydrolisis in catfish (Clarias gariepinus) saucefermentation. The crude bromelin enzym extracted from fruit of pineapple. Crude bromelainenzym concentration which used for this research was 3% (B3), 6% (B6), and 9% (B9). The bestconcentration of crude bromelain enzym for catfish sauce quality was B9, because producedhighest hydrolisat volume and protein content which was 99.67 ml, 77.86% (bk) respectively.Total oganoleptic value which made with 9% concentration of crude enzym bromelain the wasmost favorable by consumer acceptance with 5.21 colour value, 4.36 taste value, 8.07 texturevalue and 5.91 odor value.Keywords : Fermentation , catfish ( Clarias gariepinus ), Crude bromelain enzym,fish sauce